SEGMEN VOKOID BAHASA MADURA DIALEK KANGEAN - Yani, Ahmad; Sudarso, Hendra (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2018)
This study aims to reveal the vocabulary segments of the Kangean dialect of the Madurese language. The linguistic phenomenon in the islands is unique and is supported by historical, demographic, and sociocultural aspects of population heterogeneity (Madura, Java, Bali, Bajo, and Mandar). Cultural acculturation has given rise to linguistic aspects in Kepualau Kangean which has its own style, namely the Madura language of the Kangean dialect which is different from the three dialects in the relic areas such as Sumenep, Pamekasan, and Bangkalan. The Kangean dialect is also different from fourteen other dialects in East Java. The question in this study is how do the forms of vocabulary in the Madurese language of the Kangean dialect? Data collection uses the documentation method with recording and recording techniques. The data analysis method used is a descriptive comparative method with dialectometric techniques and isogloss files. The results showed that there were 13 vocoid segments, the whole could represent phonetics, but from these 13 phonetics only six could represent themselves as phonemists, namely /a/ /i/ /u/ /e/ /o/ dan /Ç/ The phonetic 13th form is [a, É, Ã£, i, Éª, e, É›, Î, u, o, É”, É”Ìƒ, Ç]